The night library - Zeltser, David (Random House, 2019)
The Polar Express meets The Night at the Museum in this fantastical picture-book adventure about the magic of books and libraries, perfect for book lovers of all ages! After a young boy goes to sleep upset that he's getting a book for his birthday, he's visited in the night by Patience and Fortitude, the two stone lions who guard the New York Public Library. Soon, he's magically whisked away from his cozy home in the Bronx, and the two mighty lions show him the wonder of the library. There, the inquisitive Latino boy discovers the power of books and their role not only in his own life, but also in the lives of the people he loves.